Minimally Processed Refrigerated Fruits and Vegetables - Yildiz, Fatih; Wiley, Robert C.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2017)
The first edition of Minimally Processed and Refrigerated Fruits and Vegetables, edited by Robert C. Wiley and Fatih Yildiz, was published in 1994. At the time of publication, this was a new concept and was well-received by the scientific community. Minimally processed foods are whole plant tissues (the identity of the plant tissue is recognized by consumers), which may contain active enzymes, live tissues, and plant cells. These are some of the basics for the healthy food design. The overall function of these foods is to provide convenient (ready-to-serve, ready-to cook, free of any pesticides and contaminants),like-fresh products for food service and retail consumers. Minimally Processed and Refrigerated Foods (MPR) have been popular in many countries. The following are some of the advantages offered by MPR produce foods: 1. Ease of portion control in the food service industry 2. Lower transportation cost (all inedible portions of the produce are removedprior to transportation) 3. No waste is generated at the point of consumption 4. Utilization and recycling of the waste is much easier 5. Value-added new fruit and vegetable products and meal development is possible and easy 6. No requirement is needed for phytosanitary control during trade 7-No glycation end products formation during processing, 8.Degree of food processing is minimized for optimal health of human, the processing plant for MPR produce, which is not addressed in any other books on this topic, will be described in this second edition. Also, comparison of minimal processing technologies with other technologies was explained in the first publication and will be updated in this second edition. During the last 200 years the purpose of food processing was a-safety(sterilization, Pasteurization,1804 Nicholas Apert,Pasteur 1867), and b-prevention of deficiency diseases(Enrichments),but MPR foods provides a two new dimensions to food processing ; a-Prevention of chronic diseases(bioactive compounds) and b-Optimum health (functional foods,Superfoods,Neutraceuticals, and Medical foods) for human.
Part 1. Fundamentals -- Chapter 1. Introduction to Minimally Processed Refrigerated (MPR) Fruits & Vegetables -- Chapter 2. Aspects of Biology and Physics Underlying Modified Atmosphere Packaging -- Chapter 3. Initial Preparation Handling, and Distribution of Minimally Processed Refrigerated Fruit and Vegetables -- Chapter 4. Enzymes in Minimally Processed Fruits and Vegetables -- Chapter 5. Biological and Biochemical Changes in Minimally Processed Refrigerated Fruits and Vegetables -- Chapter 6.Preservation Methods for Minimally Processed Refrigerated Fruits and Vegetables -- Chapter 6. Packaging and Preservation of Minimally Processed Refrigerated Produce -- Part 2. Commodities -- Chapter 8. Postharvest Quality and Safety of Fresh-cut Vegetables -- Chapter 9. Fresh-cut Fruits -- Chapter10. Minimally processed herbs, spices, medicinal and aromatic, plants -- Chapter 11. Sprouts, Microgreens, and Baby leafs -- Chapter 12. Minimally Processed Mushrooms -- Chapter 13. Minimal Processing of Tropical and Subtropical Fruits, Vegetables, Nuts and seeds -- Chapter 14. Minimally processed fresh green beverage industry: Smoothies, Shakes and Frappes -- Chapter 15. Fermented Vegetables -- Part 3. New Technologies -- Chapter 16. New Technologies and Edible Coatings for MPR Fruits and Vegetables -- Chapter 17. Use of Geographical Information Technologies in a Precision Agriculture Management System for Food Traceability -- Chapter 18. DNA Barcoding for MPR Fruits and Vegetables -- Part 4. Health and Food Safety -- Chapter 19. Microorganisms Found in/on of MPR Packaged Produce and Their Detection Methods -- Chapter 20. Comparison of HACCP and ISO 22000 in the ready to eat fruit and vegetable Industry in conjunction with application of Failure Mode and Effect Analysis (FMEA) and Ishikawa diagrams -- Chapter 21. Health and Physiological Bioactive Compounds in Fruits and Vegetables -- Chapter 22. Environmental Impacts of Minimally Processed Refrigerated Fruits and Vegetables Industry.
Keywords: Chemistry; Chemistry